2014
DOI: 10.1016/j.gheart.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

World Heart Federation Expert Consensus Statement on Antiplatelet Therapy in East Asian Patients with ACS or Undergoing PCI

Abstract: Guideline recommendations on the use of dual antiplatelet therapy (DAPT) in patients with acute coronary syndromes and in those undergoing percutaneous coronary intervention (PCI) have been formulated by both the ACC/AHA and the ESC. These recommendations are based primarily on large, phase III, randomized, controlled trials of the P2Y12 inhibitors clopidogrel, prasugrel, and ticagrelor. However, few East Asian patients have been included in the trials to assess the use of these agents, particularly the newer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
104
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 67 publications
1
104
1
Order By: Relevance
“…Fourth, a previous study showed the "East Asia paradox": East Asian patients had fewer ischemic events after PCI compared with Western patients. 16 Kumar et al 17 reported that the rate of composite adverse event endpoints after stent implantation for the Asian population, including death or MI, was lower than that for Caucasians, even after adjusting for risk factors. However, the GRACE discharge score still showed long-term out-of-hospital prognostic value for the mortality of patients with SCAD after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, a previous study showed the "East Asia paradox": East Asian patients had fewer ischemic events after PCI compared with Western patients. 16 Kumar et al 17 reported that the rate of composite adverse event endpoints after stent implantation for the Asian population, including death or MI, was lower than that for Caucasians, even after adjusting for risk factors. However, the GRACE discharge score still showed long-term out-of-hospital prognostic value for the mortality of patients with SCAD after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of studies in the US, the reported bleeding rate was higher in Asian‐Americans compared to Caucasian‐Americans treated with percutaneous coronary intervention for acute coronary syndrome . A previous report has suggested that East Asians have different risk profiles for bleeding compared with Caucasians, and that a different “therapeutic window” of on‐treatment platelet reactivity might be appropriate in East Asians . Optimal antiplatelet or anticoagulant therapies during TAVI for Asian populations should be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a prospective observational study reported that the ischemic and bleeding event rates were similar between Japanese ACS patients at high bleeding risk receiving a low-maintenance dose of prasugrel and those at non-high bleeding risk receiving a standard maintenance dose of prasugrel [12]. However, given the known marked interethnic differences in the pharmacokinetic and pharmacodynamic profiles between prasugrel and clopidogrel [1,2], the findings of these studies [11,12] may not be applicable to other ethnic groups. Further studies are necessary to examine the efficacy and safety of a step-down regimen or a low-dose prasugrel regimen in various ethnic populations.…”
Section: Discussionmentioning
confidence: 96%
“…Clopidogrel and prasugrel are P2Y12 inhibitors, thienopyridine antiplatelet agents. Prasugrel is a new-generation agent that inhibits platelet aggregation more potently and exerts therapeutic action faster Ivyspring International Publisher than clopidogrel [1,2]. Clopidogrel and prasugrel show markedly different pharmacokinetic and pharmacodynamic profiles.…”
Section: Introductionmentioning
confidence: 99%